Cyber Forensic Reporting: Benefits, Elements, Process, Expert Witnesses, and Ethical Considerations - Alexander, Cheryl Ann; Wang, Lidong (International Journal of Criminology and Sociology, 2025)
Cyber forensic reporting creates a complete and evidence-based record. Appropriate cyber forensic reporting includes the investigation process with compliance and legal evidence, analysis, findings, and actionable recommendations for legal admissibility. In healthcare, cyber forensic reporting helps improve compliance with regulations such as the Health Insurance Portability and Accountability Act (HIPAA) and facilitates the detection of vulnerabilities. This paper deals with cyber forensic reporting, which includes its benefits, elements, and process; expert witnesses; and ethical considerations. Cyber forensic reporting in healthcare is introduced. Expert witnesses in healthcare cyber forensic reporting are significant. There is a need for the right experts, including experts with specialized experience and knowledge in both healthcare and digital forensics.